Drug-induced hyponatraemia in psychogenic polydipsia. - Gossain, V. V. (BMJ Group, 1976)
Two patients with psychogenic polydipsia developed hyponatraemia, one in association with administration of hydrochlorothiazide and the other with that of tolbutamide. It is suggested that the increased fluid intake in such patients may make them more susceptible to the development of hyponatraemia from thiazide or sulphonylurea compounds.